Rational molecular targeting of the inter-subunit interaction between human cardiac troponin hcTnC and hcTnI using switch peptide-competitive biogenic medicines. (August 2020) - Xiao, Danrui; Fan, Zixun; Jiaqi, Wu; Liu, Hua; Shen, Linghong; He, Ben; Zhang, Min
Graphical abstract: Highlights: Biogenic competitors are used to competitively disrupt human cardiac hcTnC–hcTnI interaction. A multistep screening protocol is performed against a biogenic compound library to identify competitors. Small-molecule collismycin and compound e are identified as potent competitors. Both competitors and hcTnI switch peptide share a common binding site of hcTnC. Abstract: The human cardiac troponin (hcTn) has been implicated in diverse cardiovascular diseases (CDs). The protein function is regulated by the inter-subunit interaction between the N-terminal domain of hcTnC and the C-terminal switch peptide of hcTnI; disruption of the interaction has been recognized as a potential therapeutic strategy for CDs. Here, we report use of biogenic medicines as small-molecule competitors to directly disrupt the protein–protein interaction by competitively targeting the core binding site (CBS) of hcTnC NTD domain. A multistep virtual screening protocol is performed against a biogenic compound library to identify competitor candidates and competition assay is employed to verify the screening results. Consequently, two compounds Collismycin and Compound e are identified as strong competitors (CC50 < 10 μM) with hcTnI for hcTnC CBS site, while other tested compounds are found to have moderate (CC50 = 10–100 μM), low (CC50 > 100 μM) or no (CC50 = N.D.) potency. The competitor ligands are anchored at the core groove of hcTnC CBS site through aromatic and hydrophobic interactions, while few peripheral hydrogen bonds are formed to further confer specificity for domain–compound recognition. These molecular-level findings would benefit from further in vitro and in vivo studies at cellular and animal levels, which can help to practice the ultimate therapeutic purpose.